DESIGN AND TEST OF A SUPPORT CUTTING ANTI-CLOGGING DEVICE WITH VIBRATION FOR A NO-TILL SEEDER - Mengnan Yin; Wenjun Wang; Yulong Chen; Long Zhou; Mingwei Li (Engenharia Agrícola)
ABSTRACT The anti-clogging device of a no-till seeder is an important component that affects the seeding quality. In one year two crop area of China, a no-tillage seeder for corn generally includes a passive anti-clogging device, and there are often problems with straw winding around working parts due to the low straw cleaning rate. To solve these problems, a support cutting anti-clogging device with vibration for a no-till seeder was designed in this study to efficiently cut wheat stalks and remove them to the sides of the seedbed. Through theoretical calculations and kinematic analysis, the main structural parameters of the device were limited to small ranges of values: the mounting angle of the vibrating knife was in the range θ1 = 70–82°, the amplification was in the range l1 = 14–24 mm, and the frequency was in the range ωm = 240–340 rad/min. To analyse the effects of the main parameters on the average straw cutting rate, soil bin experiments were carried out using an orthogonal multinomial regressive experimental design with three factors and three levels. The optimal structural parameters derived in this way were as follows: mounting angle for the vibrating knife θ1 = 70.7°, amplification l1 = 19 mm, and frequency ωm = 330.2 rad/min. The results of adaptability and comparison tests showed that the average straw cutting rate was 93.30% when the proposed anti-clogging device with vibration was used. Compared to traditional devices, the cutting rate for the device was increased by 12.82%, and the metrics were superior to those of a traditional anti-clogging device. This research can serve as a reference for designing anti-clogging devices for no-till seeders.